Amending the Alaska native claims settlement act [microform] : hearing, Ninety-third Congress, second session, on H.R. 12355 . - United States. Congress. House. Committee on Interior and Insular Affairs. Subcommittee on Indian Affairs. (Washington : U.S. Govt. Print. Off., 1974)
Reuse of record except for individual research requires license from Congressional Information Service, Inc. "Serial no. 93-41." CIS Microfiche Accession Numbers: CIS 74 H441-14 Microfiche. Mode of access: Internet.